Potret Kemiskinan dan Upaya Penanggulangannya Melalui Program Perlindungan Sosial di Kawasan Terpencil Banyuwangi Selatan - Nur Hidayati (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
This study aims to (1) identify portrait of poverty in the remote area of ??Erpach, (2) portrait of poverty in the remote area of ??Soponyono, (3) identify poverty reduction efforts through social protection programs. The approach used is a qualitative approach, the type of research uses qualitative descriptive type. The results of this study indicate that the factors that cause poverty in the Erpach and Soponyono regions are the first structural and cultural poverty, the two education age communities do not have school motivation because of the distance and the difficult terrain, the third is the low skills of the community to manage potential in the area, the fourth is the lack of public education, the fifth part of the community lives around the forest and the coast. The mitigation efforts, first held the FGD (Focus Group Discussion), the second carried out the SAS social protection program (Peer Care) in cooperation with the village government with the local government, thirdly the skills training in managing the potential of the region in cooperation with the Cooperative and UMKM Office (Micro Business, Small and Medium) Banyuwangi district, and all four education programs are obliged to learn to cooperate with the Education Office